Factors Associated With Functional Decline in Hand and Hip/Knee Osteoarthritis After One Year: Data From a Population‐Based Study. Issue 9 (27th July 2021) - Siviero, Paola; Limongi, Federica; Gesmundo, Antonella; Zambon, Sabina; Cooper, Cyrus; Dennison, Elaine M.; Edwards, Mark H.; van der Pas, Suzan; Timmermans, Erik J.; van Schoor, Natasja M.; Schaap, Laura A.; Dallmeier, Dhayana; et al.
Abstract : Objective: To investigate factors that together with hand or hip/knee osteoarthritis (OA) could contribute to functional decline over a year's time in elderly individuals. Methods: The data of 1, 886 individuals between ages 65 and 85 years in a prospective, observational population‐based study with 12–18 months of follow‐up in the context of the European Project on Osteoarthritis were analyzed. The outcome measures were self‐reported hand and hip/knee functional decline, evaluated using a minimum clinically important difference of 4 on the Australian/Canadian Hand OA Index and of 2 on the Western Ontario and McMaster Universities Osteoarthritis Index hip/knee physical function subscales, both normalized to 0–100. Using regression models adjusted for sex, age, country, and education level, the baseline factors considered were clinical hand or hip/knee OA, pain, analgesic/antiinflammatory medications, comorbidities, social isolation, income, walking time, grip strength, physical activity time, and medical/social care. Results: After a year, 453 participants were identified as having worse hand functionality and 1, 389 as not worse. Hand OA, anxiety, walking time, and grip strength were risk factors for hand functional decline; pain was a confounder of the effect of hand OA. Analgesic/antiinflammatory medications mediated the combined effect of hip/knee OA plus pain on functional decline in the 554 individuals classified as having worse hip/knee functionality and the 1, 291 persons who were not worse. Peripheral artery disease, obesity, and cognitive impairment were other baseline risk factors. Conclusion: Study findings showed that together with emotional status and chronic physical and cognitive conditions, OA affects hand and hip/knee functional decline.